2001
DOI: 10.1385/endo:14:2:225
|View full text |Cite
|
Sign up to set email alerts
|

Hyperleptinemia in Pregnant Bats Is Characterized by Increased Placental Leptin Secretion In Vitro

Abstract: Hyperleptinemia is a common feature of pregnancy in mammals. The source of increased plasma leptin is uncertain. We examined leptin secretory rates in vitro to test the hypothesis that leptin secretion is upregulated during pregnancy. Two species of insectivorous bats were examined, Myotis lucifugus and Eptesicus fuscus, because of their unique reproductive cycle. Body mass and plasma leptin significantly increased with gestation and decreased during lactation. Adiposity increased in midgestation, then decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…All mammals thus far investigated, including humans, showed increased serum leptin level during mid-to late-pregnancy (Gavrilova et al 1997, Masuzaki et al 1997, Kunz et al 1999, Zhao et al 2003. Contrary to the non-pregnant mammals, elevated leptin levels of pregnancy in mammals are not usually correlated with adiposity (Kronfeld-Schor et al 2001). In baboons, bats, and humans, the placenta is a major source of circulating leptin level during pregnancy (Hoggard et al 2000, Kronfeld-Schor et al 2001.…”
Section: Role Of Leptin In Bat Ovarymentioning
confidence: 99%
See 1 more Smart Citation
“…All mammals thus far investigated, including humans, showed increased serum leptin level during mid-to late-pregnancy (Gavrilova et al 1997, Masuzaki et al 1997, Kunz et al 1999, Zhao et al 2003. Contrary to the non-pregnant mammals, elevated leptin levels of pregnancy in mammals are not usually correlated with adiposity (Kronfeld-Schor et al 2001). In baboons, bats, and humans, the placenta is a major source of circulating leptin level during pregnancy (Hoggard et al 2000, Kronfeld-Schor et al 2001.…”
Section: Role Of Leptin In Bat Ovarymentioning
confidence: 99%
“…Contrary to the non-pregnant mammals, elevated leptin levels of pregnancy in mammals are not usually correlated with adiposity (Kronfeld-Schor et al 2001). In baboons, bats, and humans, the placenta is a major source of circulating leptin level during pregnancy (Hoggard et al 2000, Kronfeld-Schor et al 2001. The conservation of hyperleptinemia during pregnancy across mammalian orders implies a fundamental role of leptin either in the maintenance of pregnancy or preparation for lactation (Kronfeld-Schor et al 2000).…”
Section: Role Of Leptin In Bat Ovarymentioning
confidence: 99%
“…Serum leptin concentrations increase dramatically during pregnancy in every mammalian species studied thus far [3,24,25,26,27]. This is due in part to high concentrations of estrogen, which stimulates leptin production.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that peripheral signals of the energetic state, with leptin concentration as the main indicator, provide the brain with information that translates to neuropeptide expression levels that, in turn, control the response to the energetic state (even though there are many examples of disassociation between plasma leptin concentrations and body mass, body fat, and energetic state, e.g., Refs. [33][34][35]. One of the major sites of leptin activity in the brain is the arcuate nucleus of the hypothalamus, where orexigenic neuropeptides such as neuropeptide Y (NPY) and agouti-related protein (AgRP), and the anorexigenic proopiomelanocortin (POMC) and cocaine and amphetaminerelated transcript (CART) expression levels change in response to information from the periphery [reviewed by Schwartz et al (52)].…”
mentioning
confidence: 99%